1991
DOI: 10.1007/bf02390363
|View full text |Cite
|
Sign up to set email alerts
|

Conization for CIN associated with human papillomavirus infection

Abstract: We report results of follow-up by PAP smears and colposcopy in 116 women treated since 1981 by conization for cervical intraepithelial neoplasia with human papillomavirus infection (HPV-CIN). The mean follow-up time was 31.9 (SD 19) months. Preoperative diagnosis was HPV-CIN II (with extension into the endocervix) in 11 cases and HPV-CIN III in 103 cases; two diagnostic conizations were performed. The histological examination of the cone biopsies showed complete excision of CIN in 109 cases (94%). Three patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Association of the three parameters were related to recurrence (AOR 9.0, P=0.0000004), reinforcing the idea of co-operation between factors increasing the risk of developing CINs and cancer. Some authors described that 90% of the patients achieved a two-year cure by using treatment procedures similar to ours: cauterization and conization (Yliskoski et al 1991), contrasting to the 80% of cure showed by us in a five-year study. These observations could be attributed to the different periods of analysis, or to the higher frequency of oncogenic HPVs detected in our patients what could be responsible for these lower efficiency in achieving cure.…”
Section: Discussioncontrasting
confidence: 52%
“…Association of the three parameters were related to recurrence (AOR 9.0, P=0.0000004), reinforcing the idea of co-operation between factors increasing the risk of developing CINs and cancer. Some authors described that 90% of the patients achieved a two-year cure by using treatment procedures similar to ours: cauterization and conization (Yliskoski et al 1991), contrasting to the 80% of cure showed by us in a five-year study. These observations could be attributed to the different periods of analysis, or to the higher frequency of oncogenic HPVs detected in our patients what could be responsible for these lower efficiency in achieving cure.…”
Section: Discussioncontrasting
confidence: 52%